Switchgrass growth and forage quality trends provide insight for management. Issue 2 (21st March 2019) - Sena, Kenton L.; Goff, Ben; Davis, David; Smith, S. Ray
Abstract : Switchgrass has been identified as a valuable crop for biomass and liquid biofuels, as a viable summer forage for cattle, and as a dual‐use crop for both applications. The objective of this research was to evaluate trends throughout the growing season in biomass and forage quality of two switchgrass cultivars in central Kentucky over a two‐year period. Earn 1 CEU in Crop Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/640 .